Methodological Approaches to Improving the Mechanism of Strategic Management in the Development of the National Food Supply System - Mikhail A. ANANIEV (Communications of International Proceedings, 2021)
Based on the foregoing, it can be concluded that the assessment of the mechanism of strategic management of the national food supply system should consider the influence of quantitative and qualitative parameters in the indicated areas and can be used to substantiate program-targeted measures at the federal, regional, municipal and economic levels of management of the development of the food supply system.
Keywords: National Food Supply System; Sustainable Functioning; Facility Management Mechanism; Organizational and Managerial Factors.